High-Performance Photodetector Based on Organic-Inorganic Perovskite CH3NH3PbI3/ZnO Heterostructure - Upadhyay R.K.; Singh A.P.; Upadhyay D.; Ratan S.; Kumar C.; Jit S. (My University, 2025)
In this letter, organic-inorganic hybrid perovskite CH3NH3PbI3-based heterostructure photodetector is fabricated on fluorine-doped tin oxide (FTO) substrate. The perovskite CH3NH3PbI3 and metal oxide ZnO are synthesized using the sol-gel chemical route. The synthesized hybrid perovskite CH3NH3PbI3 has a tetragonal phase with a crystallite size of 39.01 nm, whereas ZnO has a wurtzite hexagonal structure with a crystallite size of 26.47 nm. The uniform distribution of particles is found in the thin film of CH3NH3PbI3 and ZnO with an average particle size of 50 and 30 nm, respectively. An efficient photoluminescence band is observed at 1.59 eV in CH3NH3PbI3 thin film measured at ambient condition and excited with light of wavelength 405 nm. The heterostructure is formed between perovskite and ZnO, which also work as an efficient electron transport layer. The heterostructure is characterized using I - V and C - V measurements that confirm the formation of the barrier between CH3NH3PbI3 and ZnO. The photoresponsivity of 21.8 A/W is obtained at an applied bias voltage of -1 V under the illumination of light obtained from monochromator of wavelength 436 nm and intensity sim 190μ textW /cm2. © 1989-2012 IEEE.